Impact of agricultural farms on the environment of the Puck Commune: Integrated agriculture calculator—CalcGosPuck - Lidia Dzierzbicka-Glowacka; Stefan Pietrzak; Dawid Dybowski; Michał Białoskórski; Tadeusz Marcinkowski; Ludmiła Rossa; Marek Urbaniak; Zuzanna Majewska; Dominika Juszkowska; Piotr Nawalany; Grażyna Pazikowska-Sapota; Bożena Kamińska; et al. (PeerJ, 2019)
Background Leaching of nutrients from agricultural areas is the main cause of water pollution and eutrophication of the Baltic Sea. A variety of remedial actions to reduce nitrogen and phosphorus losses from agricultural holdings and cultivated fields have been taken in the past. However, knowledge about the risk of nutrient leaching has not yet reached many farmers operating in the water catchment area of the Baltic Sea. Methods The nutrient balance method known as “At the farm gate” involves calculating separate balances for nitrogen (N), phosphorus (P) and potassium (K). After estimating all the components of the nutrient balance, the total balance for NPK is calculated and the data obtained is expressed as the ratio of total change (surplus) to the area of arable land on a farm. In addition, the nutrient usage efficiency on a farm is also calculated. An opinion poll was conducted in 2017 on 3.6% (n = 31) of the farms located in commune of Puck. The total area of the farms including arable and grass land ranged from 5 to 130 ha with an average of 45.82 ha. The arable land was on average 30.79 ha ranging from 4.45 to 130 ha while the grassland averaged 12.77 ha and ranged from 0 to 53 ha. Results The average consumption of mineral fertilizer in the sample population of farms was 114.9 kg N, 9.3 kg P, and 22.9 kg K·ha−1of agricultural land (AL), respectively. N balance in the sample farms being ranged from −23.3 to 254.5 kg N·ha−1AL while nutrient use efficiency ranged from 0.40% to 231.3%. In comparison, P surplus in the sample farms was 5.0 kg P·ha−1AL with the P use efficiency of 0.4–266.5%. Discussion Mean N fertilizer consumption in the tested farms was higher than the average usage across Poland and in the Pomeranian Voivodeship. However, mean consumption of potassium fertilizers was lower than mentioned averages. Mean P fertilizer consumption was higher than in the Pomeranian Voivodeship, but lower compared to the entire country. Generally, on the basis of designated research indicators of farm pressures on water quality, concentrations of total nitrogen and total phosphorus were obtained. CalcGosPuck (an integrated agriculture calculator) will help to raise farmers’ awareness about NPK flow on farm scale and to improve nutrient management.